Analysis of Double Skin Composite Slabs - Husain M. Husain; Mohannad H. Al-Sherrawi; Asmaa Taha Ibrahim (Journal of Engineering, 2018)
This paper deals with finite element modeling of the ultimate load behavior of double skin composite (DSC) slabs. In a DSC slab, shear connectors in the form of nut bolt technique studs are used to transfer shear between the outer skin made of steel plates and the concrete core. The current study is based on finite element analysis using ANSYS Version 11 APDL release computer program. Experimental programmes were carried out by the others, two simply supported DSC beams were tested until failure under a concentrated load applied at the center. These test specimens were analyzed by the finite element method and the analyses have shown that these slabs displayed a high degree of flexural characteristics, ultimate strength, and ductility. The close agreement has been observed between the finite element and experimental results for ultimate loads and load–deflection responses. The finite element model was thus found to be capable of predicting the behavior of DSC slabs accurately.